Targeting Metabolic Enzymes in Cancer – Clinical Trials Update - O’Neal, Julie; Chesney, Jason (Current Enzyme Inhibition, 2013)
The uptake and utilization of glucose and glutamine by cancer cells are markedly higher than by most nontransformed, normal epithelial and mesenchymal cells. This metabolic shift enables the production of ATP and anabolic precursors necessary for the synthesis of proteins, lipids and nucleotides required for survival, proliferation and invasiveness. The observations that certain oncogenic proteins (Ras, c-Myc and HIF-1α) and tumor suppressors (p53, PTEN, Rb and VHL) regulate the expression and activity of several metabolic enzymes have supported their potential as molecular targets for the development of anti-neoplastic agents. Indeed, recent pre-clinical studies have shown that several established and novel inhibitors of metabolic enzymes exhibit reasonable therapeutic indices when tested in xenograft models of tumorigenesis. In this review, we will discuss the rationale of targeting metabolic enzymes for the treatment of cancer and then will describe published pre-clinical and clinical data for several inhibitors of metabolism in cancer.
Keywords: chemotherapy